Human Factors Analysis and Classification System (HFACS) on Accidents Due to Tilting Ship - Dewi Kurniasih; Aditya Maharani; Mochamad Luqman Ashari (Institute of Advanced Knowledge and Science, 2024)
The transportation industry is the main point of the distribution of goods and passengers. Data shows the number of shipwrecks is very high. The accident was caused by many factors, one of which was the tilting of the ship. The research starts from categorizing the causes of ship accidents through existing secondary data, FGD with expert judgments to find the root of the problem and also looking for what mitigations can be done so that similar incidents do not repeat. And the analysis is made in the Human Factors Analysis and Classification System (HFACS) method. The results of this study indicate that there are human factors in recurring events at all stages of HFACS such asunsafe acts, the preconditions for unsafe acts, unsafe supervision and organisational influences. For the stages of unsafe acts are Skill based Errors, decision errors, Perceptual Errors, and Exceptional. For the stage of the preconditions for unsafe acts are technological environment, physical environment, and adverse mental state; and for the stage of unsafe supervision is the lack of supervision; for organizational influences there are resource management and organizational climate.